Comparing Ocular Responses to Caloric Irrigation and Electrical Vestibular Stimulation in Vestibular Schwannoma - Mackenzie, Stuart W.; Iriving, Richard; Monksfield, Peter; Dezso, Attila; Dawe, Nicholas; Lindley, Karen; Reynolds, Raymond F. (Frontiers in Neurology, 2019)
Electrical Vestibular Stimulation (EVS) is a non-invasive technique for activating the vestibular-ocular reflex, evoking mainly a torsional eye movement response. We have previously demonstrated that this response can be used to detect vestibular asymmetry in patients with vestibular schwannoma (VS). Here we perform a direct comparison of EVS with caloric irrigation in this patient group. We studied 30 patients with unilateral VS, alongside an equal number of aged-matched healthy control subjects. EVS current was delivered to the mastoid process in a monaural configuration using a sinusoidal stimulus (2 Hz; ± 2 mA; 10 s), with an electrode placed over the spinous C7 process. Evoked eye movements were recorded from the right eye in darkness using an infra-red sensitive camera while the subject sat relaxed with their head on a chinrest. Ocular torsion was subsequently tracked off-line using iris striations. Each subject separately underwent water caloric irrigation, in accordance with the British Society of Audiology guidelines. For the caloric test, eye movement was recorded in the yaw axis using electro-oculography. For both EVS and calorics, inter-aural response asymmetry was calculated to determine the extent of canal paresis. Both tests revealed impaired vestibular function in the ipsilesional ear of VS patients, with a mean asymmetry ratio of 15 ± 17% and 18 ± 16% for EVS and calorics, respectively. Overall, the caloric test results discriminated controls from patients slightly more effectively than EVS (Cohen's D effect size = 1.44 vs. 1.19). Importantly, there was a significant moderate correlation between the AR values produced by EVS and calorics (r = 0.53, p < 0.01), and no significant difference between mean AR estimates. When questioned, ≥85% of participants subjectively preferred the EVS experience, in terms of comfort. Moreover, it took ~15 min to complete, vs. ~1 h for caloric. These results confirm that the results of the EVS test broadly agree with those of caloric irrigation, in terms of detecting vestibular asymmetry. Furthermore, they suggest a higher degree of convenience and patient comfort.